2006
DOI: 10.1136/emj.2006.041160
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards resuscitation in New Zealand high-school students

Abstract: Background: Introducing cardiopulmonary resuscitation (CPR) training in the high-school curriculum has been widely recommended as a long-term strategy to educate the wider community. Although CPR has been included in the New Zealand school curriculum, it is listed as an optional subject only. Aim: To assess the attitude towards and knowledge of CPR in 16-17-year-old high-school students in New Zealand. Methods: Questionnaires were administered to 494 students aged 16-17 years across six high schools in Welling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 9 publications
5
63
3
2
Order By: Relevance
“…20 However, high school students in a New Zealand study 21 reported an even higher willingness to provide BLS to a family member than the Norwegian students in the present study. Compared to slightly younger high school students in the USA 18 our students were more reluctant to perform rescue breathing on a child, but more willing to resuscitate a family member, intravenous drug user and trauma victim.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…20 However, high school students in a New Zealand study 21 reported an even higher willingness to provide BLS to a family member than the Norwegian students in the present study. Compared to slightly younger high school students in the USA 18 our students were more reluctant to perform rescue breathing on a child, but more willing to resuscitate a family member, intravenous drug user and trauma victim.…”
Section: Discussioncontrasting
confidence: 72%
“…In recent studies, the willingness to perform CPR varies considerably among high school students in e. g. Japan 20 and New Zealand. 21 To investigate knowledge of CPR and attitude to performing bystander CPR among young Norwegians, we questioned secondary school students about CPR training, self-reported experience with cardiac arrest situations, and how they think they would react in given cardiac arrest situations.…”
Section: Introductionmentioning
confidence: 99%
“…The results of current study showed that radiology technologists participating in the study generally had a positive attitude towards CPR (80 ± out of 115), and a correlation was also observed between attitude towards CPR and technical knowledge. On the contrary, the technical knowledge of participants was poor (average 8.8 ± 2.3 of 17), which was in contrast with the findings of Parnell et al (20) who showed that students with a positive attitude toward CPR and first aid acquired a higher technical knowledge score than those with a negative attitude. But it was in line with the findings of Aaberg et al (16) and Giri et al (21).…”
Section: Discussioncontrasting
confidence: 80%
“…Importantly, none of surveyed teachers achieved an excellent result. Parnell and collaborates [24] conducted a study to assess the attitude towards and knowledge of CPR among 494 high-school students 16 -17-years of age in New Zealand. Poor theoretical knowledge (mean score 5.61 ± 2.61 out of a maximum score of 18) was recorded.…”
Section: Introductionmentioning
confidence: 99%